Adaptation and validation of the questionnaire based on the Index for Inclusión: teachers and inclusion in Santiago Chile - Elizabeth Jashes Morgues, Jessana; González Castellano, Nuria; Colmenero Ruiz, Mª Jesús (Revista Complutense de Educación, 2024)
INTRODUCTION. This paper shows the process of analysis and adaptation of the Questionnaire on Educational Inclusion applied to a group of teachers from three schools in Santiago de Chile. The first version of the questionnaire was prepared based on the self-assessment guide for Inclusive Education Index for Inclusion by Booth and Ainscow (2011), which consisted of 37 items organized into 3 dimensions and 4 subdimensions, in addition to sociodemographic data. METHOD. To build the questionnaire, 45 items from the Index were selected based on the research objectives and validated through expert judgment, leaving 37 items on a Likert scale with 4 response alternatives. The questionnaire was applied to a group of 116 regular teachers, 31 differential teachers and 19 support professionals corresponding to the 3 school levels: Preschool or Kindergarten Education, Basic Education and Secondary Education. RESULTS: The data were subjected to an internal consistency study and exploratory factor analysis (AFE) and confirmatory factor analysis (AFC), which allowed the questionnaire to be reduced to 22 items, which were organized into 4 dimensions: development of inclusive practices, inclusive actions of the school, inclusive relationships and inclusive school resources and supports. DISCUSSION: This questionnaire constitutes a reliable and pertinent tool for the Chilean context, since it allows generating significant information regarding the key strategies to address diversity from the premise that there must be quality education for all.
Keywords: Educational inclusion; Teacher; Questionnaire; Factorial analysis; Validation